Phylogenetic analysis of Ukrainian seed-transmitted isolate of Soybean mosaic virus - Mishchenko, L.T.; Dunich, A.A.; Shcherbatenko, I.S. (Вiopolymers and Cell, 2018)
Soybean mosaic virus (SMV) is seed transmitted and can cause significant reductions in the yield and seed quality in soybean (Glycine max). The seed transmission rate of different SMV isolates is 0–43 %. The question regarding SMV genes involved in the seed transmission of its isolates remains open. The phylogenetic studies of Ukrainian seed-transmitted SMV isolates have not been conducted. Aim. Phylogenetic analysis of the CP gene region of the SMV isolate, which has the ability to seed transmission. Methods. RNA extraction from plant material, RT-PCR, sequencing, phylogenetic analysis. Results. For the first time, the phylogenetic analysis of 430 nt CP gene sequence of seed-transmitted SMV isolate SKS-18 was performed. The highest level of the nucleotide sequences identity (98.8 %) and amino acid sequences (98.6 %), the isolate SKS-18 has with the Iranian isolates Ar33, Lo3, American isolate VA2, and Ukrainian isolate UA1Gr. Two unique amino acid substitutions (Ser→Cys at position 1 and Lys→Ala at position 2) in the studied CP gene region of SKS-18 are revealed. Conclusions. The isolate SKS-18 is localized in the same cluster with the isolates of the highest nucleotide identity, that may be due to their similar variability. Unique amino acid substitutions in the studied CP gene region of SKS-18 can be involved to its seed transmission and other important functions of the infectious cycle, the identification of which is necessary for the development of effective plant protection measures against viral diseases.